Biochemical Properties of Xylose Reductase Prepared from Adapted Strain of Candida tropicalis - M. Rafiqul, Islam; Mimi Sakinah, A. M. (Springer, 2014)
Xylose reductase (XR) is an intracellular enzyme, which catalyzes xylose to xylitol conversion in the microbes. It has potential biotechnological applications in the manufacture of various commercially important specialty bioproducts including xylitol. This study aimed to prepare XR from adapted strain of Candida tropicalis and to characterize it. The XR was isolated from adapted C. tropicalis, cultivated on Meranti wood sawdust hemicellulosic hydrolysate (MWSHH)-based medium, via ultrasonication, and was characterized based on enzyme activity, stability, and kinetic parameters. It was specific to NADPH with an activity of 11.16 U/mL. The enzyme was stable at pH 5–7 and temperature of 25–40 °C for 24 h and retained above 95 % of its original activity after 4 months of storage at −80 °C. The Km of XR for xylose and NADPH were 81.78 mM and 7.29 μM while the Vmax for them were 178.57 and 12.5 μM/min, respectively. The high Vmax and low Km values of XR for xylose reflect a highly productive reaction among XR and xylose. MWSHH can be a promising xylose source for XR preparation from yeast.